2005
DOI: 10.1149/1.2013047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Electrocatalytic Activity of Antimony-Doped Tin Dioxide Anodes toward the Oxidation of Phenol in Aqueous Solutions

Abstract: Antimony-doped tin dioxide electrodes supported on titanium have been used in the electrochemical treatment of aqueous solution containing phenol. Ti/SnO 2 -Sb anode has high efficiency in the elimination of phenol, but its use is hindered by its short service life. The introduction of platinum in the oxide layer ͑3 or 13 atom %͒ increases the electrode service life up to two orders of magnitude. The electrocatalytic activity of the electrodes toward phenol oxidation has been analyzed with respect to the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 35 publications
2
52
0
1
Order By: Relevance
“…Correa-Lozano et al [41] reported a service life of less than 12 h for Ti/SnO 2 -Sb 2 O 5 anodes at a current density 100 mA cm -2 when used for the electrolysis of aqueous acidic solutions. The deactivation of these electrodes has been proposed to be due to the formation of a nonconductive tin hydroxide in the outer layer of the anode [42,43]. Chen et al [44] reported that Ti/SnO 2 -Sb 2 O 5 anodes underwent some irreversible damage within seconds, as measured by ability to treat chemical oxygen demand, although they were still able to treat COD by 75% in subsequent usage.…”
Section: Anode Longevitymentioning
confidence: 99%
“…Correa-Lozano et al [41] reported a service life of less than 12 h for Ti/SnO 2 -Sb 2 O 5 anodes at a current density 100 mA cm -2 when used for the electrolysis of aqueous acidic solutions. The deactivation of these electrodes has been proposed to be due to the formation of a nonconductive tin hydroxide in the outer layer of the anode [42,43]. Chen et al [44] reported that Ti/SnO 2 -Sb 2 O 5 anodes underwent some irreversible damage within seconds, as measured by ability to treat chemical oxygen demand, although they were still able to treat COD by 75% in subsequent usage.…”
Section: Anode Longevitymentioning
confidence: 99%
“…In fact, even when coated with films, the Ti substrate can be oxidized either during the preparation process or when working as an anode, due to film porosity that makes the electrode permeable to oxygen. Therefore, to avoid TiO 2 interlayer formation, which presents high resistivity, many studies have been performed and several proposals have been presented, including the addition of Pt to the SnO 2 film [33][34][35][36], a prior platinization of the Ti substrate followed by SnO 2 deposition [37], an addition of IrO 2 or a isomorphous structure interlayer [7,[38][39][40][41] or a RuO x [41] or Sb 2 O x interlayer [42,43] between the Ti and SnO 2 . All of these procedures increased the lifetime of the electrodes, in some cases up to two orders of magnitude longer [38].…”
Section: Introductionmentioning
confidence: 99%
“…Although anodes with a high overpotential for oxygen evolution (i.e. doped SnO 2 [13] -or doped Diamond [14]) present higher current efficiency in conversion processes, the use of conductive metal oxide anodes (including mixed oxides) has been reported in many scientific works [15][16][17][18] due to their availability, synthesis reproducibility and dimensional stability. This last factor is crucial in waste water treatment applications.…”
Section: Direct Oxidationmentioning
confidence: 99%